INTANGIBLE CULTURE RELATED TO CRAFTSMANSHIP (Eureka Journal of Humanities and Social Research, 2026)
This article highlights the types of intangible cultural heritage associated with the manufacture of wooden products in crafts, including shelves, chests, khantakhta, various boxes, chairs, cradles, spinning wheels, axes, keli, juva, chekich, wooden bowls, and carts. The article discusses the intangible cultural heritage associated with wood, as well as the preservation and transformation processes of values and unique traditions passed down from generation to generation.
Keywords: Crafts, intangible cultural heritage, shelves, chests, khantakhta, various boxes, chairs, cradles, spinning wheels, axes, keli, juva, chekich, wooden bowls, ox carts, camel carts and donkey carts, international crafts festival, wooden shovels, patron saints, traditions, ceremonies.